Predicting large solar flares with data assimilation. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Strugarek, Antoine; Charbonneau, Paul
Abstract: We propose to use a deterministically-driven class of self-organized criticality sandpile models to carry out predictions of the largest, most dangerous, and hardest to predict solar flares.